2017
DOI: 10.1155/2017/1738085
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Vehicle Temporal and Spatial Travel Behavior Using License Plate Recognition Data

Abstract: Understanding travel patterns of vehicle can support the planning and design of better services. In addition, vehicle clustering can improve management efficiency through more targeted access to groups of interest and facilitate planning by more specific survey design. This paper clustered 854,712 vehicles in a week using K-means clustering algorithm based on license plate recognition (LPR) data obtained in Shenzhen, China. Firstly, several travel characteristics related to temporal and spatial variability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…To identify the commuting vehicles, a clustering technique was utilized to analyze temporal-spatial features extracted from ALPR data. Many clustering algorithms and strategies, such as K-means [24,31], DBSCAN [32], GMM (Gaussian Mixture Model) [33], nested clustering [34], online agglomerative clustering [35], hierarchical clustering [36], and other algorithms [37,38] had been proposed in the past decades. Hierarchical clustering, as a typical unsupervised machine learning algorithm, has been applied to a wide spectrum of transportation researches.…”
Section: Commuting Vehicles Identification Using Ward's Hierarchical mentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the commuting vehicles, a clustering technique was utilized to analyze temporal-spatial features extracted from ALPR data. Many clustering algorithms and strategies, such as K-means [24,31], DBSCAN [32], GMM (Gaussian Mixture Model) [33], nested clustering [34], online agglomerative clustering [35], hierarchical clustering [36], and other algorithms [37,38] had been proposed in the past decades. Hierarchical clustering, as a typical unsupervised machine learning algorithm, has been applied to a wide spectrum of transportation researches.…”
Section: Commuting Vehicles Identification Using Ward's Hierarchical mentioning
confidence: 99%
“…Recently, with the emerging big data technologies [13], the commuting pattern at an individual level can be efficiently derived using advanced data-driven methods (e.g., machine learning) [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Various kinds of data were utilized in these data-driven based methods, including Global Positioning System (GPS) data, mobile phone call detail records (CDRs), smart card data and remote sensing imagery [14][15][16], which provide new sights for traffic control-oriented applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park [5] found that several clustering methods such as the K-means and Fuzzy clustering were effective in traffic volume forecasting. Chen et al [6] used the K-means clustering along with Davies-Bouldin Index and Silhouette Coefficient to capture the distinct groups in the vehicle temporal and spatial travel behaviors using license plate recognition data. Fuzzy C-means clustering, a probability-based clustering was found successful in recognizing congestion patterns on urban roads based on GPS trajectory [7].…”
Section: Review Of Clustering Applicationsmentioning
confidence: 99%
“…However, scant attention has been paid to mining human travel patterns with AVI data in previous research. Chen et al clustered several travel characteristics such as travel distance, travel frequency, and total activity duration using the K-Means clustering algorithm based on AVI and presented a detailed analysis of each group [30]. Their result showed that it is possible to identify vehicle groups with similar travel behavior using AVI data.…”
Section: Literature Reviewmentioning
confidence: 99%